Topical Antibiofilm Agents With Potential Utility in the Treatment of Chronic Rhinosinusitis: A Narrative Review - Hale, Samuel J. M.; Wagner Mackenzie, Brett; Lux, Christian A.; Biswas, Kristi; Kim, Raymond; Douglas, Richard G. (Frontiers in Pharmacology, 2022)
The role of bacterial biofilms in chronic and recalcitrant diseases is widely appreciated, and the treatment of biofilm infection is an increasingly important area of research. Chronic rhinosinusitis (CRS) is a complex disease associated with sinonasal dysbiosis and the presence of bacterial biofilms. While most biofilm-related diseases are associated with highly persistent but relatively less severe inflammation, the presence of biofilms in CRS is associated with greater severity of inflammation and recalcitrance despite appropriate treatment. Oral antibiotics are commonly used to treat CRS but they are often ineffective, due to poor penetration of the sinonasal mucosa and the inherently antibiotic resistant nature of bacteria in biofilms. Topical non-antibiotic antibiofilm agents may prove more effective, but few such agents are available for sinonasal application. We review compounds with antibiofilm activity that may be useful for treating biofilm-associated CRS, including halogen-based compounds, quaternary ammonium compounds and derivatives, biguanides, antimicrobial peptides, chelating agents and natural products. These include preparations that are currently available and those still in development. For each compound, antibiofilm efficacy, mechanism of action, and toxicity as it relates to sinonasal application are summarised. We highlight the antibiofilm agents that we believe hold the greatest promise for the treatment of biofilm-associated CRS in order to inform future research on the management of this difficult condition.